Antigenic expression and spontaneous immune responses support the use of a selected peptide set from the IMA950 glioblastoma vaccine for immunotherapy of grade II and III glioma - Dutoit, Valérie; Herold-Mende, Christel (OncoImmunology, 2018)
Gliomas are lethal brain tumors that resist standard therapeutic approaches. Immunotherapy is a promising alternative strategy mostly developed in the context of glioblastoma. However, there is a need for implementing immunotherapy for grade II/III gliomas, as these are the most common CNS tumors in young adults with a high propensity for recurrence, making them lethal despite current treatments. We recently identified HLA-A2-restricted tumor-associated antigens by peptide elution from glioblastoma and formulated a multipeptide vaccine (IMA950) evaluated in phase I/II clinical trials with promising results. Here, we investigated expression of the IMA950 antigens in patients with grade II/III astrocytoma, oligodendroglioma or ependymoma, at the mRNA, protein and peptide levels. We report that the BCAN, CSPG4, IGF2BP3, PTPRZ1 and TNC proteins are significantly over-expressed at the mRNA (n = 159) and protein (n = 36) levels in grade II/III glioma patients as compared to non-tumor samples (IGF2BP3 being absent from oligodendroglioma). Most importantly, we detected spontaneous antigen-specific T cell responses to one or more of the IMA950 antigens in 100% and 71% of grade II and grade III patients, respectively (27 patients tested). These patients displayed T cell responses of better quality (higher frequency, broader epitope targeting) than patients with glioblastoma. Detection of spontaneous T cell responses to the IMA950 antigens shows that these antigens are relevant for tumor targeting, which will be best achieved by combination with CD4 epitopes such as the IDH1R132H peptide. Altogether, we provide the rationale for using a selective set of IMA950 peptides for vaccination of patients with grade II/III glioma.
Gesehen am 18.10.2018
Published online: 07 Nov 2017